Biomechanical effects of high heeled shoes on neck pain among females – a narrative review - Tahir Mahmood; Naqvi , Rubab; Waseem , Iqra; Salam, Abdul (Journal of the Pakistan Medical Association, 2022)
Neck pain is the fourth leading cause of disability, and is the most common musculoskeletal disorder. High-heel shoes, one of the significant identities of females, cause pain in the neck as well as in feet and ankle regions. The current narrative review was planned to explore evidence to highlight the biomechanical factors of high-heel shoes as the source of neck pain, which mostly remains undiagnosed. PubMed and Google Scholar search engines were explored for full text of research articles published in English language from 2016 to 2021. Of the 82 studies initially found, 22(27%) were shortlisted for full-text assessment, and, of them, 6 (27.27%) were selected for detailed analysis. Despite other contributing factors, kinematics and kinetics should be considered primarily during neck pain management. Based on best available evidence, high heels increase the individual’s height, but result in significant decrease in trunk flexion. —Continue